Type 2 diabetes mellitus in obesity promotes prolongation of cardiomyocyte contractile function, impaired Ca2+ handling and protein carbonylation damage - Coelho, Priscila M.; Simmer, Luísa M.; da Silva, Daniel S.; dos Santos, Matheus C.; Kitagawa, Rodrigo R.; Pezzin, Mateus F.; Corrêa, Camila Renata [UNESP]; Leite, Jéssica G. [UNESP]; Leopoldo, André S.; Lima-Leopoldo, Ana Paula (Elsevier, 2023)
Aims: To investigate whether the obesity associated to T2DM presented cardiomyocyte myocardial contractility dysfunction due to damage in Ca2+ handling, concomitantly with increased biomarkers of oxidative stress. Methods: Male Wistar rats were randomized into two groups: control (C): fed with standard diet; and obese (Ob) that fed a saturated high-fat. After the characterization of obesity (12 weeks), the Ob animals were submitted to T2DM induction with a single dose of intraperitoneal (i.p.) injection of streptozotocin (30 mg/kg). Thus, remained Ob rats that were characterized as to the presence (T2DMOb; n = 8) and/or absence (Ob; n = 10) of T2DM. Cardiac remodeling was measured by post-mortem morphological, isolated cardiomyocyte contractile function, as well as by intracellular Ca2+-handling analysis. Results: T2DMOb presented a significant reduction of all fat pads, total body fat and adiposity index. T2DMOb group presented a significant increase in protein carbonylation and superoxide dismutase (SOD) activity, respectively. T2DMOb promoted elevations in fractional shortening (15.6 %) and time to 50 % shortening (5.8 %), respectively. Time to 50 % Ca2+ decay was prolonged in T2DMOb, suggesting a possible impairment in Ca2+recapture and/or removal. Conclusion: Type 2 diabetes mellitus in obesity promotes prolongation of cardiomyocyte contractile function with protein carbonylation damage and impaired Ca2+ handling.
Keywords: Calcium handling; Contractile function; Oxidative stress; Type 2 diabetes mellitus in obesity